Physiological Studies and Yield of Different Mustard Genotypes under Saline Water Irrigation in Semi-arid Region of Haryana - Prakash, Ram; Devi, Sarita; Rani, Sarita; Jat, Mukesh Kumar; Dhanda, Ankush; Meena, R.L. (Journal of Soil Salinity and Water Quality, 2024)
The present study was undertaken to identify a salt-tolerant mustard variety suitable for the semi-arid region. This particular region faces a significant challenge due to abundance of low-quality water for irrigation. The accumulation of nutrients in a saline environment represents the primary hindrance to achieving sustainable crop production. Three different water qualities ECiw (Canal, 2.5 and 7.5 dS m-1) were applied to evaluate the eleven mustard varieties. Among the eleven mustard genotype CSCN 220-10 gave the highest seed yield (23.7qha-1) and the lowest seed yield (15.0 qha-1) was obtained in variety Kranti at ECiw 7.5 dS m-1. The overall mean reduction in yield at 2.5, 5.0 and 7.5 dS m-1was 3.31, 14.12 and 23.34%, respectively as compared to canal. The entire range of characteristics i.e. seed yield, plant height, number of branches and siliqua per plant, chlorophyll content (SPAD units) and photochemical quantum yield (Fv/Fm) exhibited a consistent decline as salinity levels increased from canal to 7.5 dS m-1. Salinity susceptibility index (SSI) indicated the varietal tolerance when values